Inclusion of soil carbon lateral movement alters terrestrial carbon budget in China - Zhang, Haicheng (Sci Rep, 2014)
The lateral movement of soil carbon has a profound effect on the carbon budget of terrestrial ecosystems; however, it has never been quantified in China, which is one of the strongest soil erosion areas in the world. In this study, we estimated that the overall soil erosion in China varies from 11.27 to 18.17 Pg yr(−1) from 1982 to 2011, accounting for 7–21% of total soil erosion globally. Soil erosion induces a substantial lateral redistribution of soil organic carbon ranging from 0.64 to 1.04 Pg C yr(−1). The erosion-induced carbon flux ranges from a 0.19 Pg C yr(−1) carbon source to a 0.24 Pg C yr(−1) carbon sink in the terrestrial ecosystem, which is potentially comparable in magnitude to previously estimated total carbon budget of China (0.19 to 0.26 Pg yr(−1)). Our results showed that the lateral movement of soil carbon strongly alters the carbon budget in China, and highlighted the urgent need to integrate the processes of soil erosion into the regional or global carbon cycle estimates.